“Diseño De Una Estrategia Educativa Sobre Signos Y Síntomas De Alarma En Gestantes En Situación Migratoria" (2023)
Design an educational strategy on the identification of warming signs in pregnant women in migratory situation. Method: Descriptive study carried out in 2 phases, the first on review of the literature in unexchanged databases, obtaining 20 articles on multimedia strategies in health promotion, and 10 articles on warning signs in pregnancy, level of knowledge and maternal-perinatal complications. The Data corresponding to content analysis and highlights were grouped by categories.